The differential binding and biological efficacy of auxin herbicides. Issue 4 (16th December 2022) - Prusinska, Justyna; Uzunova, Veselina; Schmitzer, Paul; Weimer, Monte; Bell, Jared; Napier, Richard M.
Abstract: Background: Auxin herbicides have been used for selective weed control for 75 years and they continue to be amongst the most widely used weed control agents globally. The auxin herbicides fall into five chemical classes, with two herbicides not classified, and in all cases it is anticipated that recognition in the plant starts with binding to the Transport Inhibitor Response 1 (TIR1) family of auxin receptors. There is evidence that some classes of auxins act selectively with certain clades of receptors, although a comprehensive structure–activity relationship has not been available. Results: Using purified receptor proteins to measure binding efficacy we have conducted quantitative structure activity relationship (qSAR) assays using representative members of the three receptor clades in Arabidopsis, TIR1, AFB2 and AFB5. Complementary qSAR data for biological efficacy at the whole‐plant level using root growth inhibition and foliar phytotoxicity assays have also been analyzed for each family of auxin herbicides, including for the afb5‐1 receptor mutant line. Conclusions: Comparisons of all these assays highlight differences in receptor selectivity and some systematic differences between results for binding in vitro and activity in vivo . The results could provide insights into weed spectrum differences between the different classes of auxin herbicides, as well as the potential resistance and cross‐resistance implications for this herbicide class. © 2022 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : The natural auxin indoleacetic acid inside its binding pocket in the receptor TIR1. Synthetic auxin herbicides bind with variable affinities which do not all correlate with herbicide efficacies.